Suture lasso combined with lateral plate in comminuted transolecranon fracture-dislocations of the elbow - Tongtong Li; Zengliang Wang; Guoyun Bu; Shucai Bai; Chen Li; Fei Chen; Peng Yang; Xuelei Wei (BMC Surgery)
Abstract Objective The objective of this study was to evaluate the effectiveness of suture lasso combined with lateral plate in comminuted transolecranon fracture-dislocations of the elbow. Method We retrospectively reviewed 13 patients with comminuted transolecranon fracture-dislocations of the elbow. Our study included 6 males and 7 females with a mean of age 54.3 years. All the patients had comminuted fracture of proximal ulna and coronoid fracture of Regan-Morrey type II/III. Among them, 4 cases were combined with radial head fractures. The patients were treated with open reduction and internal fixation with suture lasso combined with lateral plate based on the traditional mode. Results The mean follow-up was 15.7 ± 5.8 months (range 12–33 months). During the follow-up period, the fracture and joint alignment were good, and there was no loosening of internal fixation. X-ray films showed that the fracture healing time was 3–6 months, with an average of 3.8 ± 0.9 months. Mild postoperative heterotopic ossification was observed in 2 cases. There was 1 case of poor wound healing and 1 case of ulnar nerve stimulation. At the last follow-up, the average Mayo elbow function score and Broberg-Morrey score were 91.5 ± 9.2 and 94.7 ± 6.5 points respectively. The result was classified as excellent in 9, good in 3, and fair in 1 patient. The excellent and good rate was 92.3%. Conclusions Our study suggested that suture lasso combined with lateral plate based on the traditional internal fixation mode was highly effective for the treatment of transolecranon fracture-dislocations of the elbow. Especially for the patient with comminuted proximal ulna, the restoration and fixation of coronoid process were quite important to increase the stability of the elbow joint and lead to good clinical efficacy.